The effect of problem based blended learning (PB2L) learning model on basic programming learning outcomes in terms of students' computational thinking skills - Paramitha, Citra Pratiwi; Samani, Muchlas; Buditjahjanto, I.G.P. Asto; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2022)
The main problem in the learning process of basic programming in the classroom is the lack of available time allocation, considering that basic programming material is very complex and there are also practicum activities and program demos. So, with the existing allocation, it is not optimal if it is used for learning activities in basic programming subjects. This can be seen in the average student learning outcomes which are always low. This study aims to determine the effect of the problem based blended learning (PB2L) model on basic programming learning outcomes in terms of students' computational thinking skills. This research was conducted through a literature review and relevant research results and continued through a Focus Group Discussion (FGD). From the research, it was found that there was a significant positive effect between the variables of the problem based blended learning (PB2L) model, student learning outcomes and computational thinking skills, which means that student learning outcomes can be improved through the application of problem based blended learning (PB2L) models and students' computational thinking skills.